COMPARATIVE STUDY OF FRUITFULNESS OF COW INSEMINATION OF A MILKING HERD AT VARIOUS LEVELS OF PRODUCTIVITY IN THE CONDITIONS OF BAYSERKE-AGRO LLP - Bekenov Dauren Maratovich,; Spanov Abzal Abushakipovich,; Chindaliyev Askhat Erbosynovich,; Baimukanov Aidar Dastanbekouly,; Sultanbai Darina Tavaldievna,; Zhaksylykova Gulnur Kenesbekovna,; Kalimoldinova Asel Sanatkyzy, (Academic Journal of Physical and Chemical Sciences, 2019)
A comparative analysis of the fruitfulness of cow artificial insemination of milking herd at various levels of productivity was carried out in the conditions of Bayserke-Agro LLP. A study of reproduction performance of the milking herd was conducted based on the results of work performed from January 2018 to March 2019. The comparative data include cows artificially inseminated both according to the natural estrous cycle and according to the hormonal stimulation scheme of the estrus according to the Ovsynch program. It was established that the variability of the insemination index is directly dependent on the level of cow productivity, while the variability of this indicator in terms of lactation numbers has not been established. The service period and the insemination index in high productive groups significantly exceed the optimal indicators, and in groups with milk yields of 6–9 thousand kg, relatively high reproductive qualities are observed, corresponding to zootechnic norms.